The Role of Capital Adequacy Ratio in Enhancing Regional Development Banks' Stability: An Empirical Study from 2012-2022 - Aziz, Lukmanul Hakim; Siregar, Hermanto; Achsani, Noer Azam; Irawan, Tony (Green Publisher Indonesia, 2025)
This study aims to analyze the role of the Capital Adequacy Ratio (CAR) in moderating factors affecting the stability (Z-score) of Regional Development Banks (BPD) in Indonesia from 2012 to 2022. Using quarterly panel data regression, this research categorizes BPDs into two groups: Category-1 banks that have not met the minimum capital requirements and Category-2 banks that have met these requirements. The findings reveal significant differences in how various factors influence stability across these categories. In Category-1 banks, factors such as market competition (Lerner Index), market share of loans (MSL), and deposits (MSD) have a more pronounced impact on stability, highlighting their reliance on external conditions. Conversely, Category-2 banks exhibit greater resilience, with CAR positively contributing to stability, while factors like efficiency (TEF and SEF) and macroeconomic conditions (regional GDP) play a crucial role in risk management. The study also finds that factors such as Loan to Deposit Ratio (LDR) and Non-Performing Loans (NPL) affect stability differently across categories, emphasizing the need for tailored risk management strategies. These insights provide practical implications for policymakers and banking management in optimizing regulatory frameworks and enhancing the stability of BPDs.